Comparative analysis of rumen metagenome, metatranscriptome, fermentation and methane yield in cattle and buffaloes fed on the same diet - Malik, Pradeep K.; Trivedi, Shraddha; Kolte, Atul P.; Mohapatra, Archit; Biswas, Siddharth; Bhattar, Ashwin V. K.; Bhatta, Raghavendra; Rahman, Habibar (Frontiers in Microbiology, 2023)
A study to compare the rumen microbial community composition, functional potential of the microbiota, methane (CH4) yield, and rumen fermentation was conducted in adult male cattle and buffaloes fed on the same diet. A total of 41 phyla, 169 orders, 374 families, and 1376 microbial genera were identified in the study. Bacteroidetes and Firmicutes were the two most abundance. The CH4 yield (g/kg DMI), CH4 emission (g/kg DDM), dry matter (DM) intake, and rumen fermentation were not vary between the two host species. Overall, the study established a substantial difference between the compositional abundances and metabolic functionality of the rumen microbiota; however, feeding cattle and buffaloes on the same diet resulted in similar microbiota composition, metabolic functionality, and CH4 yield. Further studies are warranted to investigate the effect of different diets and environments on the composition and metabolic functionality of the rumen microbiota.